Implementation of Law Enforcement and Immigration Control of Foreign Citizens - Ilham Zico Pratama; Welby Ilham Muwaffaq; Sadra Tri Agraeny (Faculty of Law, University of Mataram, 2021)
Immigration is an agency that has the authority to carry out supervision of the traffic of anyone entering and leaving the territory of Indonesia. the Indonesian government opened immigration channels as an effort to increase the country's foreign exchange to increase economic growth. So that the government can grant visa freedom only by giving the stamp and initials given by the official. This is what is often misused by some foreign nationals who do activities in Indonesia that are not in accordance with the immigration rules that have been set. This study aims to describe law enforcement and immigration control of foreign nationals in Samarinda. In the implementation that has been running so far it has been quite good, but has not produced maximum results. To fulfill this goal, there will be 3 ways to supervise foreign countries, namely: Administrative Supervision, Field Supervision and PORA TEAM Coordination. This research will also describe several laws related to immigration law enforcement for foreign nationals.